Amnesty in Latin America: a systematic review - Trujillo Poveda , Mentor Filimon (2025)
Amnesty is a phenomenon of historical and contemporary relevance in the resolution of political and social conflicts. The purpose of this article was to describe the state of research on amnesty in Latin America. The methodology employed consisted of a qualitative systematic review following the PRISMA method. Twelve articles were selected after a search of the Web of Science, Scopus, SciELO, Dialnet, and Redalyc databases. The results reveal the complexity and duality of amnesty, as it can facilitate reconciliation and political transition, but also generate impunity and injustice for victims of human rights violations. It involves power relations and social dynamics, requiring legal frameworks adapted to the historical and social realities of each country. Future research should delve deeper into its long-term impacts, incorporate the voices of victims, and adopt multidisciplinary approaches to strengthen restorative justice and democracy in the region.